Catalytic activation of formic acid using Pd nanocluster decorated graphitic carbon nitride for diclofenac reductive hydrodechlorination - Feng Shao; Yixuan Gao; Wenhui Xu; Fengbin Sun; Long Chen; Li, Fan; Liu, Wen (Journal of Hazardous Materials, 2023)
Halogenated pharmaceuticals exhibit high toxicity if released to natural environment, and dehalogenation is a key process for their degradation. In this study, a reductive and directional dehalogenation technique, heterogenous formic acid (HCOOH) catalytic activation system, was proposed for diclofenac (DCF) dechlorination and detoxification. A functional material of Pd nanocluster decorated graphitic carbon nitride (Pd/g-C3N4) was developed for HCOOH activation. Although the optimized material (Pd1/g-C3N4) showed lower HCOOH decomposition rate (k1 = 0.287 ± 0.017 min−1) than the pristine Pd particles (k1 = 0.401 ± 0.031 min−1), it processed higher DCF degradation efficiency (97.9% within 30 min) than Pd particles. The enhancement mechanism was revealed by both experiments and theoretical calculations. Firstly, the six-fold cavities of g-C3N4 acted as anchor sites, which offered strong coordination environment for Pd nanoclusters. Secondly, the strong coordination environment of Pd led to upshifted d-band center of Pd 4d with enhanced bonding state, and then promoted HCOOH adsorption on Pd/g-C3N4, thus facilitating HCOOH decomposition through formate pathway rather than carboxyl pathway. Thirdly, Pd/g-C3N4 ensured HCOOH selectively decomposed as dehydrogenation reaction, which generated more H* (adsorbed H on Pd) than the dehydration reaction. The H* was proved to be the dominant reductive species for DCF hydrodechlorination. Moreover, the toxicities of DCF dechlorination products were greatly reduced.
Keywords: Catalytic reduction; Dechlorination; Diclofenac; Formic acid; Pd nanocluster